Heterochely and cheliped dimorphism in the porcellanid crab Petrolisthes japonicus (De Haan, 1849) (Decapoda: Porcellanidae) - Katsuyuki Hamasaki; Shigeki Dan (Nauplius, 2022)
Abstract Cheliped dimorphism is common in decapod crustaceans, and many decapods have a pair of different-sized chelipeds, i.e., one side being larger (major) than the other (minor), a phenomenon known as heterochely. Anomuran crabs from the family Porcellanidae exhibit a true crab-like body shape, with relatively large chelipeds for their body size, and they show a sexual size dimorphism of chelipeds (i.e., males with larger chelipeds). However, very little is known about heterochely in porcellanid crabs. Therefore, we aim to elucidate heterochely and cheliped dimorphism in the porcellanid crab Petrolisthes japonicus (De Haan, 1849). We examined the laterality of the chelipeds and performed allometric growth analyses of the cheliped dimensions. Heterochely was observed in most of the specimens, and major chelipeds occurred randomly on either the right or left sides of the body, regardless of the crab size. Major and minor cheliped size of males surpassed female cheliped size, and males increased the growth of both major and minor chelipeds to the same degree during the breeding season, thereby inducing the distinct intersexual size dimorphism of the cheliped. This is probably attributable to sexual selection (i.e., male-male competition). Intersexual dimorphism as an energy allocation strategy was also evident with females allocating their energy evenly to both major and minor cheliped growth without changing the chela shape; regardless of the body size, whereas males were investing more energy in major cheliped growth, resulting in wider chelae with increasing body size. Consequently, the major cheliped may have a greater role in male-male competition in P. japonicus.